Radiographic pelvimetry in free-ranging Eurasian lynx (Lynx lynx carpathicus) from Switzerland - Morend, Fanny; Lang, Johann; Vidondo, Beatriz; Ryser-Degiorgis, Marie-Pierre (European Journal of Wildlife Research, 2022)
The observation of pelvic anomalies in two Eurasian lynx (subspecies Lynx lynx carpathicus) from a population reintroduced to Switzerland raised the question of the frequency of such anomalies, but no anatomical reference values were available for comparison. This study aimed at providing baseline data on the pelvic morphology of Carpathian lynx from Switzerland, and at detecting potential pelvic anomalies. Measurements of 10 pelvic parameters were performed on the radiographs of 56 lynx taken from 1997–2015. Two ratios (vertical diameter/acetabula; sagittal diameter/transversal diameter) and two areas (pelvic outlet and inlet) were calculated to describe pelvic shape. The results showed that the Eurasian lynx has a mesatipellic pelvis, with a pelvic length corresponding to approximatively 20% of the body length. We found growth-related pelvis size diferences among age classes and evidence of sexual dimorphism in adults: two parameters refecting pelvic width were larger in females, likely to meet the physiological requirements of parturition. By contrast, pelvis length, conjugata vera, diagonal conjugata, sagittal diameter, and tendentially also vertical diameter, were larger in males, in agreement with their larger body size. Outliers were found in fve individuals but apparently without clinical signifcance. Extreme values were likely due to inter-individual diferences and the limited sample size rather than to possible congenital or developmental pathological morphology of the pelvic cavity. We present baseline data of the pelvic morphology, including growth and sexual dimorphism, which may be useful for health monitoring and for determination of age and sex in skeletal remains of Carpathian lynx.